Implementing Islamic Law in Diaspora Naturalization: A Middle East, Southeast Asia, and West - Hermawan, Wawan; Islamy, Mohammad Rindu Fajar; Faqihuddin, Achmad; Ulum, Miftahul (AHKAM : Jurnal Ilmu Syariah, 2025)
This study examines the implementation of Islamic law in diaspora naturalization, comparing dynamics across the Middle East, Southeast Asia, and the West. While naturalization has expanded globally due to economic integration, political participation, and security concerns, the role of Islamic law varies regionally. Using a qualitative comparative approach, this research analyzes policies in the three regions, supplemented by a Quantitative Systematic Literature Review (SLR) of Scopus-indexed journals under the PRISMA model. Findings reveal stark contrasts: In the Middle East, Islamic law is central to citizenship, particularly in religion-based status and family law, with deep integration into national legal systems. Southeast Asia adopts a more adaptive approach, prioritizing economic and skill-based naturalization while retaining Islamic principles in marriage and inheritance. Conversely, Western secular frameworks exclude formal recognition of Islamic law in naturalization, though diaspora communities often navigate dual legal realities. The study highlights how regional legal traditions, socio-political contexts, and migration policies shape these disparities. It concludes that Islamic law’s influence persists most strongly in the Middle East, remains contextually flexible in Southeast Asia, and operates informally in the West despite systemic secularization. These insights contribute to debates on religion, migration, and legal pluralism in global citizenship regimes. Abstrak:Penelitian ini mengkaji implementasi hukum Islam dalam naturalisasi diaspora dengan membandingkan dinamika di Timur Tengah, Asia Tenggara, dan Barat. Meskipun naturalisasi telah meluas secara global karena integrasi ekonomi, partisipasi politik, dan pertimbangan keamanan, peran hukum Islam bervariasi secara regional. Menggunakan pendekatan kualitatif komparatif, penelitian ini menganalisis kebijakan di ketiga wilayah, dilengkapi dengan Systematic Literature Review (SLR) kuantitatif terhadap jurnal terindeks Scopus menggunakan model PRISMA. Temuan mengungkap kontras yang tajam. Di Timur Tengah, hukum Islam menjadi sentral dalam kewarganegaraan, terutama menyangkut status berbasis agama dan hukum keluarga, dengan integrasi mendalam ke dalam sistem hukum nasional. Asia Tenggara mengadopsi pendekatan lebih adaptif, mengutamakan naturalisasi berbasis ekonomi dan keterampilan sambil mempertahankan prinsip Islam dalam perkawinan dan warisan. Sebaliknya, kerangka sekuler Barat tidak mengakui hukum Islam secara formal dalam naturalisasi, meskipun komunitas diaspora sering menghadapi realitas hukum ganda. Studi ini menyoroti bagaimana tradisi hukum regional, konteks sosio-politik, dan kebijakan migrasi membentuk disparitas ini. Disimpulkan bahwa pengaruh hukum Islam paling kuat di Timur Tengah, tetap fleksibel secara kontekstual di Asia Tenggara, dan beroperasi secara informal di Barat meski ada sekularisasi sistemik. Temuan ini berkontribusi pada debat tentang agama, migrasi, dan pluralisme hukum dalam rezim kewarganegaraan global.